Characterizing the distributions of IDO-1 expressing macrophages/microglia in human and murine brains and evaluating the immunological and physiological roles of IDO-1 in RAW264.7/BV-2 cells. - Rong Ji (Public Library of Science (PLoS), 2021)
Indoleamine 2,3-dioxygenase 1 (IDO-1) is an immunosuppressive enzyme expressed in the placenta, neoplastic cells, and macrophages to reject T cells by converting tryptophan into kynurenine. However, the role of IDO-1 in brain immunity, especially in the meninges, is unclear. We aim to elucidate the distribution pattern of IDO-1+ macrophages/microglia in the human brain tissues, human glioblastoma, APP/PS1 mouse brains, and quinolinic acid model brains and explore the physiological and immunological roles of IDO-1+ macrophages/microglia. Here, we find that both human and mouse macrophages/microglia of the perivascular and subarachnoid space and in glioblastoma (GBM) expressed IDO-1 but not macrophages/microglia of parenchyma. Using IDO-1 inhibitors including 1-MT and INCB24360, we observed that inhibiting IDO-1 reduced the cellular size and filopodia growth, fluid uptake, and the macropinocytic and phagocytic abilities of human blood monocytes and RAW264.7/BV-2 cells. Inhibiting IDO-1 with 1-MT or INCB24360 increased IL-1β secretion and suppressed NLRP3 expression in RAW264.7/BV-2 cells. Our data collectively show that IDO-1 expression in perivascular and meninges macrophages/microglia increases cellular phagocytic capacity and might suppress overactivation of inflammatory reaction.